Biomechanics of ossiculoplasty - KELLY, DANIEL; Prendergast, Patrick John (Rila, 2003)
Many different designs of prostheses are available for middle ear surgery. Clinical comparisons of such prostheses are often difficult because of the large number of variables involved in the clinical outcome; including the skill of the surgeon or patient variability. In an attempt to compare the performance of four different middle ear implants (Kurz Bell-Tubingen, Kurz Aerial-Tubingen, Xomed no.0362, Xomed no. 0321), a finite element model of the middle ear before and after ossiculoplasty was developed, based on a micro CT scan of the ossicles. The response of each prosthesis was different and could be related in part to the design of the prosthesis or its location within the middle ear. This study shows how finite element modelling might be used in optimizing the design of new middle ear prostheses.
PUBLISHED
Keywords: Mechanical & Manufacturing Engineering